Challenges and Strategies of Elementary School Teachers in Planning Character Education Based on Local Culture - Rohmah Istikomah; Suhadi (STAI At-Tahdzib, 2026)
This study aims to explore the challenges and strategies faced by elementary school teachers in planning character education based on local culture in the era of the Merdeka Curriculum. A qualitative approach with a multi-site case study design was employed at two elementary schools in East Java, involving 12 teachers as primary informants. Data were collected through in-depth interviews, observation of lesson plan development, and document analysis of school curricula. Thematic analysis was conducted to identify meaning patterns. The results reveal three main challenges: Limitations in integrating local culture into standard national Lesson Plan; insufficient teacher training on contextual approaches, and; resistance from students/parents toward non-formal materials. Teacher-developed strategies include adapting local folktales (such as the Suroboyo legend) into collaborative projects, collaboration with traditional figures, and modification of portfolio-based character assessments. These findings imply the need for strengthened teacher training and flexible school policies to enrich character education. This research contributes to developing contextual lesson planning models in elementary schools.